Pivotal role of Pharmacovigilance Programme of India in containment of antimicrobial resistance in India - Vijit Agrawal; Tarani Prakash Shrivastava; Pramod Kumar Adusumilli; Kalaiselvan Vivekanandan; Prasad Thota; Shashi Bhushan (Perspectives in Clinical Research, 2019)
Misuse of antimicrobials has become one of the grave concerns of public health. In last two decades, this has been largely contributing in the emergence of antimicrobial resistance (AMR) among all the pathogens. A 2013 report of Centres for Disease Control and Prevention, USA figured that at least 2 million people get an antibiotic-resistant infection every year and as many as 23,000 people lost their life. A multi-country survey in Southeast Asia region conducted by World Health Organization (WHO) in 2015, identified several gaps in knowledge and awareness about the optimal use of antimicrobials and AMR. Following this, the Ministry of Health and Family Welfare (MoHFW), Government of India, developed National Action Plan in the year 2017 to combat AMR. Pharmacovigilance Programme of India (PvPI) being a flagship programme of MoHFW holds the responsibility of ensuring safety of medicines used by India population and has recently identified AMR as one of the strategic priorities. This article intends to provide insights of the recent attempts and deliberate efforts made by PvPI in the containment of AMR in India and it also intends to sensitize healthcare fraternity on restricting AMR in public interest.